Functional expression of the polymeric immunoglobulin receptor from cloned cDNA in fibroblasts (The Rockefeller University Press, 1986)
The polymeric immunoglobulin receptor, a transmembrane protein, is made by a variety of polarized epithelial cells. After synthesis, the receptor is sent to the basolateral surface where it binds polymeric IgA and IgM. The receptor-ligand complex is endocytosed, transported across the cell in vesicles, and re-exocytosed at the apical surface. At some point the receptor is proteolytically cleaved so that its extracellular ligand binding portion (known as secretory component) is severed from the membrane and released together with the polymeric immunoglobulin at the apical surface. We have used a cDNA clone coding for the rabbit receptor and a retroviral expression system to express the receptor in a nonpolarized mouse fibroblast cell line, psi 2, that normally does not synthesize the receptor. The receptor is glycosylated and sent to the cell surface. The cell cleaves the receptor to a group of polypeptides that are released into the medium and co-migrate with authentic rabbit secretory component. Cleavage and release of secretory component do not depend on the presence of ligand. The cells express on their surface 9,600 binding sites for the ligand, dimeric IgA. The ligand can be rapidly endocytosed and then re-exocytosed, all within approximately 10 min. Very little ligand is degraded. At least some of the ligand that is released from the cells is bound to secretory component. The results presented indicate that we have established a powerful new system for analyzing the complex steps in the transport of poly-Ig and the general problem of membrane protein sorting.